SPERM QUALITY IN RATS PREDISPOSED TO THE MANIFESTATION OF CATATONIC REACTIONS - M. A. Kleshchev; T. A. Alekhina; L. V. Osadchuk (Вавиловский журнал генетики и селекции)
Catatonia is a psychopathological syndrome displayed as a motor disorder. Catatonia is a sign of many menthal disorders, particularly schizophrenia and depression, with a wide disrtibution in the human population. The GC (“genetic” and “catatonia”) rat strain was obtained from the Wistar rat strain by a long selection (78 generations) for the catatonic type of reaction and is a model of schizophrenic and depressive disorders in humans. It is known that selection for behavior including catatonic reactions results in neuroendocrine, reproductive and morphological changes in animals. However, the influence of selection for a catatonic reaction on the spermatogenic function of testes had not been studied. The aim of this study was to conduct a comparative investigation of sperm quality in rats of the GC and the Wistar strain. The epididymal sperm parameters (sperm count, sperm motility, sperm morphology) were measured, and body, testes and epididymal weight were determined at puberty (50 day of life) and at adulthood (90 day of life). The litter size of the GC and Wistar rats was determined. It was found that adult GC rats had a lower sperm count, sperm motility, testis weight, epydidymal weight and litter size compared to adult Wistar rats. However, at puberty, GC rats had a higher sperm count than the Wistar strain. Interstrain differences in sperm morphology were not found. It has been assumed that the changes of spermatogenic parameters in response to selection for catatonia are caused by changing the ontogenic pattern of testosterone secretion. In conclusion, the hereditary predisposition to catatonic reaction is associated with impaired sperm parameters in adult rats that reduces their chance to reproduction. The GC rat strain can be a perspective model for investigation of the relationship between the hereditary predisposition to catatonia and spermatogenesis